SGLT1/2 expression in the heart of transplanted patients is associated with inflammatory induction of oxidative stress: potential protective effect of SGLT2 inhibitors. (3rd October 2022) - Gong, D S; Mroueh, A; Matsushita, K; Fakih, W; Auger, C; Oak, M H; Pieper, M P; Morel, O; Epailly, E; Schini-Kerth, V
Abstract: Introduction: Heart transplantation is a life-saving surgical procedure for patients with end-stage cardiac dysfunction, however, such procedures are usually at risk of rejection due to acute inflammatory activation. While such inflammatory induction leaves the newly transplanted heart at risk of functional and structural remodeling subsequent to oxidative damage, current anti-inflammatory treatment options expose the patient to an elevated risk for adverse reactions in addition to absence of cardio-protective effects. Therefore, novel therapies with anti-inflammatory and cardio-protective dual effects are needed. Recently, our group has reported that low-grade inflammation is associated with upregulation of SGLT1/2 in arteries of human with cardiovascular diseases. Yet, the role and function of SGLT2 in human cardiac tissue remains poorly understood. Aim: This study focuses on the expression pattern of SGLT1/2 in cardiac biopsies of heart transplanted patients and aim to identifying their functional impact. Methods: Routine endomyocardial Biopsies (23) were performed for the detection of acute rejection heart transplanted patients (less than 2 years) at our University Hospital. Gene expression levels were assessed using RT-qPCR, the in situ tissue localization of proteins by immunofluorescence staining, and the level of oxidative stress by dihydroethidium staining. Results: Gene expression analysis revealed strong inflammatory reaction in 5 samples indicated by at least 20-fold higher levels of mRNA of IL1B, IL6, TNFA and CD68 compared to the other 18 samples and concomitant with high expression levels of SLC5A1, SLC5A2, AT1R, CYBA, NCF1, ICAM1, VCAM1, MMP2, MMP9 and TGFB1 in contrast to low levels of NOS3. In addition, increased levels of oxidative stress were observed in the same biopsies, which were diminished by the antioxidant N-acetylcysteine (NAC), NADPH oxidase inhibitor (VAS-2870), TNF-α receptor neutralizing antibody (infliximab), ACE inhibitor (perindoprilat), AT1R antagonist (losartan), dual SGLT1/2 inhibitor (sotagliflozin) and selective SGLT2 inhibitor (empagliflozin) with inhibitory effects reaching up to 80%. Immunofluorescence staining indicated signals for nitro-tyrosine, TNF-alpha, SGLT1 and 2 in several samples. Conclusion: These findings indicate that both isoforms SGLT1 and SGLT2 are expressed in the transplanted human heart and suggest a pattern of expression associated with pro-inflammatory response. They further indicate a potential protective effect of SGLT2 inhibitors in transplanted hearts through mitigating oxidative stress and hence providing a possible novel therapy for heart transplantation recipients to preserve the heart function. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim Pharma GmbH & Co. KG